2013
DOI: 10.3892/etm.2013.1285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin on the proliferation of breast cancer cells and expression of survivin in vitro

Abstract: Quercetin is a hydrophobic agent with potential anticancer activity. The aim of the present study was to observe the effects of quercetin on the proliferation of the breast cancer cell line MCF-7 and the gene expression of survivin. The molecular mechanism underlying the antiproliferative effect of quercetin was also investigated. MCF-7 breast cancer cells were treated with various concentrations of quercetin. The inhibitory effect of quercetin on proliferation was detected using the 3-(4,5-dimethylthiazol-2-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 13 publications
4
77
1
Order By: Relevance
“…In other studies, Quercetin inhibited the growth of breast cancer cells. The mechanism behind this effect could be the induction of apoptosis by triggering G0/G1 phase arrest (Deng et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, Quercetin inhibited the growth of breast cancer cells. The mechanism behind this effect could be the induction of apoptosis by triggering G0/G1 phase arrest (Deng et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the development of surgical techniques and chemotherapy, relapses occur very often especially in advanced cases (Deng et al, 2013). Therefore, the development of new antitumor substances is of paramount importance in the ongoing war against cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin treatment led to variations in survivin mRNA expressions and G 0 /G 1 phase cell cycle arrest in MCF-7 cells. All these effects depended on concentration and exposure time 84 . An in vivo experiment on the synergistic effect of quercetin with doxorubicin injected in mice with breast cancer was carried out.…”
Section: Quercetinmentioning
confidence: 99%
“…It was concluded that quercetin enhanced the anti-cancer activity of 5GG in MDA-MB-231 cells 42 . Deng et al 84 described the effects of quercetin against MCF-7 cells in laboratory conditions. Quercetin treatment led to variations in survivin mRNA expressions and G 0 /G 1 phase cell cycle arrest in MCF-7 cells.…”
Section: Quercetinmentioning
confidence: 99%